Characterization of Chemical Properties, Lipid Profile, Total Phenol and Tocopherol Content of Oils Extracted from Nine Clones of Red Fruit (Pandanus conoideus) - Sarungallo, Zita Letviany; Hariyadi, Purwiyatno; Andarwulan, Nuri; Purnomo, Eko Hari (Agriculture and Natural Resources, 2015)
Red fruit (Pandanus conoideus) is an endemic plant of Papua, Indonesia, traditionally known as a source of edible oil. The chemical properties of oil free fatty acid (FFA)—iodine value, peroxide value, phosphorus—the lipid profile—fatty acid (FA) and triacylglycerol (TAG) compositions—and the total phenol and tocopherol contents were determined for oil extracted from nine clones of red fruit cultivated in three area of Papua. Red fruit oil (RFO) was extracted using a chloroform-methanol solution (2:1). RFOs from nine clones had FFA of 4.3 to 9.2%, peroxide value of 0.36 to 0.84 meq per kg, iodine value of 79.3 to 85.5 g per 100 g and phosphorus content of 38 to 374 ppm. The main FAs of the RFOs were oleic (49.36–64.47 g per 100 g), linoleic (4.13–16.06 g per 100 g) and palmitic (14.11–19.21 g per 100 g), while the major TAG species were OOO/triolein (26.84–39.81%), POO/palmito-diolein (24.23–31.08%), OLO/linoleo-diolein (7.23–17.43%) and PLO/palmito-linoleo-olein (3.72–14.3%). The RFOs contained total phenol (90–742 ppm), total tocopherol (234–1,728 ppm), α-tocopherol (52–272 ppm) and γ-tocopherol (16–287 ppm). The results of principal component analysis confirmed that the nine clones of red fruit can be divided into three groups based on their FAs and TAGs.